REKONSTRUKSI KRITIS PEMIKIRAN GENDER DALAM ISLAM - Jonkenedi, Jonkenedi (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Islam needs critical studies to terminate bias and domination in religious interpretation. It’s including a collective process that combines study, investigation, social analysis, education, and action to investigate woman issues. We also have to give encouragement and opportunity to women to develop religious teaching interpretation that not bias to man. The goal is creating equality and radical change, with women as its core change. With this, it’s possible to cultivate critical consciousness to women gender transformation.